2020
DOI: 10.1021/acs.jmedchem.9b01900
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 4-Aminopiperidines as Inhibitors of Influenza A Viral Entry That Are Synergistic with Oseltamivir

Abstract: Vaccination is the most prevalent prophylactic means for controlling seasonal influenza infections. However, an effective vaccine usually takes at least 6 months to develop for the circulating strains. Therefore, new therapeutic options are needed for the acute treatment of influenza infections to control this virus and prevent epidemics/pandemics from developing. We have discovered fast-acting, orally bioavailable acylated 4-aminopiperidines with an effective mechanism of action targeting viral hemagglutinin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 49 publications
2
44
0
1
Order By: Relevance
“…Specific types of intermolecular interactions include hydrophobic (residues HA1-H38, HA1-Q40, HA2-W21, and HA2-I45) and polar interactions between the chlorine atoms of CBS1117 and side chains of residues HA1-T325 and HA2-T49. The importance of the polar interaction between the benzyl 2-chlorine and the HA2-T49 side chain hydroxyl is in agreement with the SAR analysis of this series of compounds, which suggested that halogen substitutions to the benzyl ring were essential for compound activity (Gaisina et al, 2020;Hussein et al, 2020). Finally, we note that characterization of the H5 HA-CBS1117 interaction by WaterLOGSY NMR confirmed compound binding to H5 HA ( Fig S2A).…”
Section: X-ray Crystallographic Structure Of the H5 Ha In Complex Witsupporting
confidence: 86%
See 4 more Smart Citations
“…Specific types of intermolecular interactions include hydrophobic (residues HA1-H38, HA1-Q40, HA2-W21, and HA2-I45) and polar interactions between the chlorine atoms of CBS1117 and side chains of residues HA1-T325 and HA2-T49. The importance of the polar interaction between the benzyl 2-chlorine and the HA2-T49 side chain hydroxyl is in agreement with the SAR analysis of this series of compounds, which suggested that halogen substitutions to the benzyl ring were essential for compound activity (Gaisina et al, 2020;Hussein et al, 2020). Finally, we note that characterization of the H5 HA-CBS1117 interaction by WaterLOGSY NMR confirmed compound binding to H5 HA ( Fig S2A).…”
Section: X-ray Crystallographic Structure Of the H5 Ha In Complex Witsupporting
confidence: 86%
“…CBS1117 has greater potency against group 1 HA strains, including circulating H1 HA and avian H5 HA (Gaisina et al, 2020;Hussein et al, 2020). Our laboratories and others have noted that HA fusion inhibitors generally exhibit group specificity.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations